Morpho-biochemical variability of indigenous jackfruits (Artocarpus heterophylus Lam.) for selection of elite types from natural populations of North–East India - Tridip Kumar Hazarika; Prakash Thapa; Panthor Debbarma; G. Karunakaran (Scientific Reports)
Abstract Crop improvement is an intricate process that involves complex interactions of several factors and can be achieved by breeding resistant varieties, adopting improved agronomic procedures, adapting to varied climatic conditions and rectifying soil nutrient levels. Leveraging existing genetic resources is a crucial component of any crop enhancement initiative. The current study aimed to ascertain the elite germplasm of jackfruit (Artocarpus heterophyllus Lam.) from their natural population in terms of physico-chemical traits from Mizoram, India. Biplot analysis was conducted using two primary principal components revealed high genetic variability among the characters like fruit weight, length and diameter, rind weight and diameter, TSS, total sugars, flakes circumference, flakes diameter and carotene. The initial principal component demonstrated noteworthy associations with fruit diameter, flakes weight with stone, flakes length, flakes circumference, rachis length, rachis diameter, ascorbic acid, non-reducing sugars, TSS, carotene and shelf life. Significant differences were seen among the 25 accessions with several groups in the ward dendrogram and scatter plot. The data obtained elucidates that the native jackfruit varieties exhibit a wide range of differences in physical and biochemical characteristics, making them valuable for selecting the best variety for future breeding programs to enhance this underutilized fruit. Our finding revealed J5, J24, J7, J18, J10 and J6 as most diverse accessions with all desirable characteristics that can be gainfully utilized as a distinct parent for future breeding programs.